Training of muslim women in Daesh digital magazines - Navarro-Granados, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this paper we analyse the education of Muslim women in the official digital magazines of the Daesh group: Dabiq and Rumiyah. We carried out a qualitative content analysis of the articles aimed at Muslim women and those in which they are specifically mentioned. We used Atlas.ti software to analyse the data. Daesh promotes a clear gender inequality, considering that Muslim women should be chaste, modest, obedient, faithful and submissive. They give her traditional roles as mother and wife. It is imperative to design preventive educational measures that include an Islamic feminist perspective.